The Influence of Transcultural Nursing Based on Health Education on Knowledge, Attitude, Mother Actions and Family Support among Breastfeeding Mother - Yulia Meiliany Naragale; Tiyas Kusumaningrum; Retnayu Pradanie (Universitas Airlangga, 2020)
Introduction: Providing additional food other than breast milk before 2-year-old babies in Kupang City are babies given